Vocational school EFL teachers’ practices of integrating ICT into English lessons: Teachers’ voices - Rodliyah, Rojab Siti (Universitas Pendidikan Indonesia, 2018)
Despite numerous studies on ICT-ELT integration, little is known about how English teachers in vocational schools in Asia and particularly in Indonesia integrate ICT into their English lessons. To fill this gap, this study aims to investigate how vocational English teachers integrate ICT into their English teaching practices in vocational high school settings. It specifically examines vocational high school English teachers’ reasons for using ICT, the ways the English teachers integrate ICT into their English lessons, and their perceptions of benefits and challenges of incorporating ICT into English classrooms. Guided by a case study design, three EFL teachers teaching at vocational high schools where ICT tools were readily available were recruited to participate in the study. Empirical data were collected through interviews and classroom observations. It was found that the teachers were self-motivated to use ICT in their English lessons due to their interests and positive attitudes towards ICT. This study also showed that the English teachers integrated ICT into their English lessons for different reasons. All the teachers agreed on the benefits of ICT-ELT integration to facilitate their learning and teaching process. They also shared the same view on the challenges they encountered when using ICT tools in the classroom. They voiced the need for training on ICT in ELT. This study highlights the importance of school support so as to promote ICT-based language teaching by providing adequate technology access and facilities as well as professional training in ICT for language teachers.